Thermal Performance Simulation of Residential Building in Tropical Climate Case Study: Housing in Bandar Universiti, Malaysia - Ratna Dewi Nur’aini (International Journal of Built Environment and Scientific Research, 2017)
Malaysia is one of country in with tropical climate that many people using air conditioning system to get indoor thermal comfort level. Computer simulation is one of method to predict the thermal performance of building. This paper focused on the thermal analysis of one storey row residential building at Bandar Universiti, Seri Iskandar, Perak, Malaysia. The objectives of this research were to investigate thermal performance of a residential building in tropical climate by Ecotect software simulation and to compare between ceramic roof, metallic roof and green roof due to temperature reduction. This research has focused on single storey terrace houses in Bandar Universiti, Seri Iskandar, Perak, Malaysia. The building model was row house for single family (livingroom-diningroom and master bedroom) and simulated using Autodesk Ecotect Analysis 2011 software. Metal roof has highest range of maximum and minimum compared with clay roof, concrete roof, and green roof. The lowest indoor air temperature was reached under green roof. Green roof can reduce indoor temperature from outdoor air temperature more and longer than clay roof, concrete roof, and metal roof. The result of simulation analysis indicated that green roof could reduce indoor temperature more than other roof types. This study suggests that green roof can be used in residential building in tropical climate.